Original paperCost-utility analysis of Ruconest® (conestat alfa) compared to Berinert® P (human C1 esterase inhibitor) in the treatment of acute, life-threatening angioedema attacks in patients with hereditary angioedema - Kawalec, Paweł; Holko, Przemysław; Paszulewicz, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Administration of human C1 esterase inhibitor (Berinert® P) from target import is the most widespread treatment strategy for patients with hereditary angioedema (HAE). However, a therapeutic health program including Ruconest ® (conestat alfa) could shorten a patient’s expectancy for a life-saving treatment. Aim: To evaluate the cost-utility of Ruconest ® (conestat alfa) financed from public funds within the newly introduced therapeutic health program compared with Berinert® P (human C1 esterase inhibitor) in the treatment of acute angioedema attacks in adults with HAE. Material and method s: The cost-utility analysis from the Polish healthcare payer’s perspective was performed for 1 year (2012). The costs and health outcomes were simulated for three pairs of eligible HAE patient groups (active treatment and corresponding placebo ). The incremental costs of each intervention compared with placebo were listed together (direct or indirect comparisons between options were impossible due to limited clinical data available). Results: The incremental cost-utility ratios (ICURs) for the evaluated interventions compared with placebo were as follows: EUR 15,226 per QALY (Ruconest ® ) and EUR 27,786 per QALY (Berinert® P). The probability of cost-utility (ICUR < EUR 24,279 per QALY) assessed for Ruconest ® administered in the case of acute angioedema attack was 61% and 41% for Berinert® P. Conclusions : The administration of Ruconest ® in acute life-threatening angioedema attacks is economically justified from the Polish healthcare payer’s perspective, results in lower costs and is characterized by higher cost-utility probability compared with Berinert® P.